جهود الشيخ عبدالرحمان حسن حبنكه الميداني الدعوية والعلمية - عموري, صبرين; رحومة, مروة; قراد, سناء (جامعة الوادي university of eloued, 2017)
الحمد لله الذي هدانا للإسلام وما كنا لنهتدي لو لا أن هدانا الله , والصلاة والسلام على نبينا محمد وعلى آله وصحبه أجمعين .... لقد حمل مشاعر الهداية من بعد رسول هذه الأمة صلى الله عليه وسلم وصحابته الكرام, العلماء والمفكرون , والدعاة المخلصون . وكان من أبرز أعلام الفكر الإسلامي والدعوة في العصر الحديث الشيخ عبد الرحمان حسن حبنكة الميداني, الذي ضرب في ميدان الثقافة الإسلامية بسهم وافر من خلال آثاره وإسهاماته في إشاعة العلم, والدأب على نشر الدعوة, وتثقيف المجتمع الإسلامي , وبما خلفه من سلاسل علمية, وهذا ما وصلنا إليه من خلال بحثنا الذي كان بعنوان "" عبد الرحمان حسن حبنكه الميداني وجهوده العلمية والدعوية"", ومن الصعوبات التي واجهتنا قلة المادة العلمية حول آثار الشيخ لوفاته الحديثة. Thesis abstract: Praise be to God who guided us to Islam and we would not guide if not God guided us and prayers and peace to our Prophet Muhammad and his family and his companions. He carried the feelings of guidance after the Messenger of this nation peace be upon him and his companions, scientists, thinkers and preachers loyal. And was one of the most prominent media of Islamic thought and advocacy in the modern era, Sheikh Abdul Rahman Hassan Habanka field, which was struck in the field of Islamic culture with abundant stock through its effects and contributions to the dissemination of science and the persistence of the dissemination of advocacy and education of the Islamic community and the successor of scientific chains This is what we reached through our research, which was titled - Abderrahmane Hassan Habanka field and his scientific and advocacy efforts - and the difficulties we faced the lack of scientific material on the effects of the Sheikh of his modern death.
دعوة